2002
DOI: 10.1046/j.1365-3059.2002.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and race characterization of Fusarium oxysporum f. sp. phaseoli isolates from Spain and Greece

Abstract: Virulence ( ≡ severity of disease) and physiological specialization of nine isolates of Fusarium oxysporum f. sp. phaseoli recovered in El Barco de Avila (Castilla y León, west-central Spain) and of two isolates from Chryssoupolis (Greece) were determined. The susceptibility/resistance response showed by a differential set of common bean cultivars ( Phaseolus vulgaris ) selected at the Centro Internacional de Agricultura Tropical (CIAT) delineated the isolates into two new races: races 6 and 7. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 17 publications
2
56
1
9
Order By: Relevance
“…Our phylogenetic analyses showed that strains from the same formae speciales can have very distinct genetic backgrounds, supporting their polyphyletic origin and confirming the observations of several studies on the origin of formae speciales of F. oxysporum (O'Donnell et al, 1998;Baayen et al, 2000;Alves-Santos et al, 2002a;O'Donnell et al, 2009). Determinants of host-specificity may be horizontally transferred between strains of F. oxysporum of different lineages, resulting in polyphyly.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our phylogenetic analyses showed that strains from the same formae speciales can have very distinct genetic backgrounds, supporting their polyphyletic origin and confirming the observations of several studies on the origin of formae speciales of F. oxysporum (O'Donnell et al, 1998;Baayen et al, 2000;Alves-Santos et al, 2002a;O'Donnell et al, 2009). Determinants of host-specificity may be horizontally transferred between strains of F. oxysporum of different lineages, resulting in polyphyly.…”
Section: Discussionsupporting
confidence: 89%
“…A wider range of symptoms was observed for strains of Fov than for Fop. Differences in aggressiveness are common among strains of F. oxysporum and can indicate the occurrence of races within formae speciales (Alves-Santos et al, 2002a;Kim et al, 2005). Since only one cultivar of each host species was used to evaluate the pathogenicity of Fov and Fop, the existence of different races among the strains in the present study could not be confirmed but the genetic diversity revealed by the phylogenetic analyses supports such possibility.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Pereira et al (2013) inoculated FOP UFV 01 in differential cultivars of beans, proposed by Woo et al (1996) and Alves-Santos et al (2002), and concluded that this isolate is a new race of the species. FOP UFV 01 inoculum was produced with PDA (potato -dextrose -agar) discs containing mycelia that were transferred to Petri dishes containing PDA.…”
Section: Reaction To Fopmentioning
confidence: 90%
“…Seven pathogen races, well-distributed across the continents, are documented in the literature. In Brazil, there are indications of the predominance of one race, designated race 2 (Alves- Santos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%